Significance of Translation Studies in Language Education: A Perspective of Post-Graduate Level Students - Bastola, Ganesh Kumar (Dristikon: A Multidisciplinary Journal, 2023)
This paper explores the perceptions and practices of postgraduate-level students about translation in language education. More specifically, it aims to examine the significance of translation studies in language pedagogy. Thus, the prime concern of this study is to see how translation is connected through language and culture to establish the relationship among and between teachers, students, curriculum and methodology. Data for the study were collected from primary sources. In doing so, the narrative inquiry method was employed in which five postgraduate-level students having translation as a specialization were purposively selected for the interview. The finding reveals that translation has an undeniable contribution to promoting language, culture and literature in our academia. The study concludes that translation assists students to theorize complex theories, approaches, and philosophies to gain in-depth knowledge and skills in relation to language pedagogy.